Examining the predictors of academic outcomes for indigenous Māori, Pacific and rural students admitted into medicine via two equity pathways: a retrospective observational study at the University of Auckland, Aotearoa New Zealand. Issue 8 (27th August 2017) - Curtis, Elana; Wikaire, Erena; Jiang, Yannan; McMillan, Louise; Loto, Robert; Poole, Phillippa; Barrow, Mark; Bagg, Warwick; Reid, Papaarangi
Abstract : Objective: To determine associations between admission markers of socioeconomic status, transitioning, bridging programme attendance and prior academic preparation on academic outcomes for indigenous Māori, Pacific and rural students admitted into medicine under access pathways designed to widen participation. Findings were compared with students admitted via the general (usual) admission pathway. Design: Retrospective observational study using secondary data. Setting:  6-year medical programme (MBChB), University of Auckland, Aotearoa New Zealand. Students are selected and admitted into Year 2 following a first year (undergraduate) or prior degree (graduate). Participants: 1676 domestic students admitted into Year 2 between 2002 and 2012 via three pathways: GENERAL admission (1167), Māori and Pacific Admission Scheme—MAPAS (317) or Rural Origin Medical Preferential Entry—ROMPE (192). Of these, 1082 students completed the programme in the study period. Main outcome measures: Graduated from medical programme (yes/no), academic scores in Years 2–3 (Grade Point Average (GPA), scored 0–9). Results: 735/778 (95%) of GENERAL, 111/121 (92%) of ROMPE and 146/183 (80%) of MAPAS students graduated from intended programme. The graduation rate was significantly lower in the MAPAS students (p<0.0001). The average Year 2–3 GPA was 6.35 (SD 1.52) for GENERAL, which was higher than 5.82 (SD 1.65, p=0.0013) for ROMPE and 4.33 (SD 1.56, p<0.0001) for MAPAS. Multiple regression analyses identified three key predictors of better academic outcomes: bridging programme attendance, admission as an undergraduate and admission GPA/Grade Point Equivalent (GPE). Attending local urban schools and higher school deciles were also associated with a greater likelihood of graduation. All regression models have controlled for predefined baseline confounders (gender, age and year of admission). Conclusions: There were varied associations between admission variables and academic outcomes across the three admission pathways. Equity-targeted admission programmes inclusive of variations in academic threshold for entry may support a widening participation agenda, however, additional academic and pastoral supports are recommended.